Alliages magnétiques dilués yttrium-terre rare et scandium-terre rare - Pureur Neto, Paulo (1984)
This thesis studies the magnetoelastic, transport and magnetic properties of single crystals of yttrium and scandium dopped with rare earth magnetic impurities. From our measurements of magnetostriction on dilute alloys we derive the magnetoelastic coefficients of the interaction between isolated ions and lattice strains. Our magnetoresistance measurements give the exchange and quadrupole coefficients of the interaction of isolated ions with the conduction electrons. The aim of our magnetic measurements is mainly to study the spin glass properties at low temperatures. The yttrium-rare earth and scandiumorare earth dilute alloys are interesting systems to probe the typical properties predicted by mean field theory for spin glasses with uniaxial crystal field.